Market Making, Prices, and Quantity Limits - Dupont, Dominique (Review of Financial Studies, 2000)
This article develops a model of spread and depth setting under asymmetric information where the equilibrium depth is proportionally more sensitive than the spread to changes in the degree of information asymmetry. The analysis uses a one-period model in which a risk-neutral, monopolistic market maker faces a price-sensitive liquidity trader and a better informed trader who is alternatively risk neutral and risk averse. The equilibrium depth can take values ranging from 0 to infinity, depending on the information asymmetry, the asset volatility, and the strength of the liquidity demand, while the spread remains positive and finite.